Strategic effects on pseudohomophone reading in phonological dyslexics with and without phonological impairment. (August 2015) - Tree, Jeremy J.; Playfoot, David
Abstract: The literature concerning reading in acquired phonological dyslexia is conflicted with regard to performance with pseudohomophones (e.g. SKOOL). While some cases are more accurate in pronouncing non-words that sound like known words than those that do not, other cases show no pseudohomophone advantage. Some cases are more successful when pseudohomophones are orthographically similar to their base words (SKOOL versus KLOO); other cases show no visual similarity effects. We collected data from two phonological dyslexics in order to examine whether pseudohomophone reading was influenced by a) the presence of a generalised phonological impairment b) whether pseudohomophones appeared alone or intermixed with non-words and c) whether the phonological dyslexic was told that pseudohomophones were included among the stimuli. Results showed that patterns of reading accuracy were different in cases with and without phonological impairment, and that altering the presentation context or providing explicit instruction affected the responses. The findings are discussed in relation to models of word reading. Highlights: We examine pseudohomophone reading in two acquired phonological dyslexia cases. Presentation context, task instructions and visual similarity factors are manipulated. Response patterns differ in cases with and without general phonological impairment. Manipulations of context and instruction altered the pattern of responses. Visual similarity effects were altered by presentation context.